2003
DOI: 10.2337/diabetes.52.10.2603
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Glomerular p47phox and p67phox by Protein Kinase C-β Activation Is Required for Oxidative Stress in Diabetic Nephropathy

Abstract: Oxidative stress is implicated to play an important role in the development of diabetic vascular complications, including diabetic nephropathy. It is unclear whether oxidative stress is primarily enhanced in the diabetic glomeruli or whether it is merely a consequence of diabetes-induced glomerular injury. To address this issue, we examined diabetic glomeruli to determine whether oxidative stress is enhanced, as well as examined the role of protein kinase C (PKC)-␤ activation in modulating NADPH oxidase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
144
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 58 publications
4
144
1
9
Order By: Relevance
“…Nevertheless, we and others have shown that NADPH oxidase is actually the predominant source of ROS in mesangial cells exposed to high glucose (16,24,63). Moreover, studies with a pharmacological NADPH oxidase inhibitor, apocynin, in streptozotocin-induced diabetic rats and in db/db mice indicate that NADPH oxidase activity is instrumental to the development of diabetic nephropathy (1,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we and others have shown that NADPH oxidase is actually the predominant source of ROS in mesangial cells exposed to high glucose (16,24,63). Moreover, studies with a pharmacological NADPH oxidase inhibitor, apocynin, in streptozotocin-induced diabetic rats and in db/db mice indicate that NADPH oxidase activity is instrumental to the development of diabetic nephropathy (1,51).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional PKC isozymes, PKC-␣ and -␤, novel PKC-␦, and atypical PKC-, phosphorylate the NADPH subunit, p47 phox , causing it to translocate to the membrane-bound NADPH subunits and activate NADPH oxidase (11,12,24,42). We and others have reported that high glucose increases the expression of the NADPH oxidase subunits, p22 phox and p47 phox , in mesangial cells in vitro and in vivo, in a PKCdependent manner (10,16,24,63). The above data prompted us to hypothesize that TGF-␤ 1 participates in early signaling promoted by high glucose in primary mesangial cells, such as NADPH oxidase activation, through an autocrine pathway.…”
mentioning
confidence: 99%
“…Per this group, the expression of p47 is about the same in the cortex versus medulla. The mesangial cells are unique in that they express Nox1, Nox4, and p22 phox , p47 phox , and p67 phox , but not Nox2 (86,127,146,164,214,223,371,380) (Fig. 6).…”
Section: Nistala Et Al 2060mentioning
confidence: 99%
“…In addition, PKC-α can enhance superoxide production via NADPH oxidase assembly with the p47phox subunit (8). Similarly, another conventional PKC isoform, PKC-β, can increase p47phox translocation and induce fibrosis (14,15).…”
mentioning
confidence: 99%
“…Melatonin selectively regulates the different PKC isoforms (16,17); only PKC-α and -β are expressed in the liver and kidneys (18); both PKC-α and PKC-β have been reported to regulate NADPH oxidase assembly (8,14); and the CAT-1 isoform is mainly responsible for l-arginine transport. Therefore, we assume that PKC-α and PKC-β are differentially regulated by melatonin on CAT-mediated l-arginine transport and NADPH oxidase-induced ROS production in the liver and kidney in rats with BDL.…”
mentioning
confidence: 99%